A review of musculoskeletal dance screening tests in collegiate dancers: a ten-year retrospective study - Watson, M. D.; Lasner, A.; Hada, N. (Journal of Dance Medicine & Science, 2025)
Introduction: Amongst dance programs, mitigating the risk of injury using comprehensive screening tests is essential. Currently, the lack of standardization for tests/measurements in screening methodology poses as the main barrier to building more effective, future screening programs for dancers. Our objective is to fill critical gaps in the existing literature on dancer screening by producing normative data, describing screening outcome changes amongst a dancer`s college career, and providing guidance to building similar screening programs.